The Application of Peppermint Essential Oil Aromatherapy for Airways Clearance is not Effective in Pulmonary Tuberculosis Patients in the Rose Room of Hospital X - Bintang Saharani; Shindi Hapsari (Jurnal EduHealth, 2026)
Tuberculosis (TB) is a pulmonary infectious disease caused by Mycobacterium tuberculosis and can lead to respiratory problems such as coughing, shortness of breath, and ineffective airway clearance. This study aimed to evaluate the effectiveness of mint leaf aromatherapy as an alternative therapy to improve airway clearance in patients with pulmonary TB in the Mawar Ward of X. A descriptive method with a nursing care approach was applied to two patients selected through purposive sampling. Mint leaf aromatherapy was administered three times daily for 15 minutes over three consecutive days. Observed parameters included respiratory rate and pattern, the presence of adventitious breath sounds, and the patient’s ability to expectorate sputum before and after the intervention. The results showed significant improvements, including normalization of respiratory rate, more regular breathing patterns, disappearance of adventitious breath sounds, and improved sputum expectoration. In conclusion, mint leaf aromatherapy has potential as an effective complementary therapy, although further studies are needed to strengthen these findings and explore the underlying mechanisms.